Perancangan Identitas Visual dan Media Promosi UMKM Novita Online Shop untuk Meningkatkan Brand Awareness - Putu Dewangga Widiawan Bandhesa; Ni Wayan Nandaryani; I Gede Yudha Pratama (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to design a visual identity and promotional media that effectively enhances the brand awareness of Novita Online Shop, a micro, small, and medium enterprise (MSME). Currently, Novita Online Shop lacks a strong visual identity and effective promotional tools to boost consumer awareness. Through observations and interviews with the MSME owner, it was found that Novita Online Shop requires a visual identity and promotional media that can increase consumer awareness and differentiate the brand from its competitors. The concept of